Classification by production: an alternative criterion to categorization - Luis Yáñez; Nidia Rojas; Ricardo Aparicio; Manuel Mazzei; Eugenio Maldonado; Jairo Fernández; Nicola Fabbozzo; Rafael Rincón; Rafael Urdaneta (Revista Científica)
At the beginning of the Genealogical Control and Registration Program, it was found that the main herds that formed the national buffalo breeding stock did not have the pertinent records for mating, even though the vast majority of this biological material had certificates of registration from their country of origin, initially from Bulgaria and India and later from Brazil and Colombia. In the absence of an institution in charge of the Stud Book, over time, this scarce information was lost to the point where it was impossible to recover it. Applying a genealogical criterion through five generations of crossbreeding by upgrading is impossible, namely, from the LA category to the PO category, with intermediate products LA1, LA2, LA3 and LA4. However, it was well known that the origin of the national inventory was mainly pure and of high genetic value, reasons for which it was considered justifiable to establish an alternative criterion, based on the simultaneous fulfillment of two principles: 1) The phenotypic approximation to the pattern of the corresponding breed; 2) Production adjusted to 244 days and standardized, as explained: LA1 0.5≤z<1; LA2 1≤z<1.5; LA3 1.5≤z. From this process, the achievements have been to: a) recognize the conformation and origin of the national buffalo herd; b) incorporate productive female buffaloes into the Program; c) consider the environmental and management conditions of each herd; d) identify situations to improve both the weighing control report and its management.